2017
DOI: 10.1523/eneuro.0381-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial Tight Junction Barrier Dysfunction Sensitizes Bladder Afferents

Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic voiding disorder that presents with pain in the urinary bladder and surrounding pelvic region. A growing body of evidence suggests that an increase in the permeability of the urothelium, the epithelial barrier that lines the interior of the bladder, contributes to the symptoms of IC/BPS. To examine the consequence of increased urothelial permeability on pelvic pain and afferent excitability, we overexpressed in the urothelium claudin 2 (Cldn2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 105 publications
(162 reference statements)
3
22
0
1
Order By: Relevance
“…Similar to the reports in human IC/BPS, a significant elevation in stretch-evoked ATP release has been demonstrated in a feline model of IC/BPS [111] and in cyclophosphamide-induced chronic (hemorrhagic) bladder inflammation in rats [129]. The high level of ATP and other urinary contents may diffuse through the leaky urothelium to sensitize bladder afferents, causing pain sensation and stimulating voiding, which are the typical symptoms of IC/BPS [130].…”
Section: Atp As a Signaling Molecule For Bladder Pain And Urgencysupporting
confidence: 78%
“…Similar to the reports in human IC/BPS, a significant elevation in stretch-evoked ATP release has been demonstrated in a feline model of IC/BPS [111] and in cyclophosphamide-induced chronic (hemorrhagic) bladder inflammation in rats [129]. The high level of ATP and other urinary contents may diffuse through the leaky urothelium to sensitize bladder afferents, causing pain sensation and stimulating voiding, which are the typical symptoms of IC/BPS [130].…”
Section: Atp As a Signaling Molecule For Bladder Pain And Urgencysupporting
confidence: 78%
“…Metabolic-cage studies in untreated, aged (>25 months) versus young adult Fischer 344 rats revealed decreases in voiding frequency ( Figure 1A ) and increases in the intervoid interval ( Figure 1B ), as well as voided volume ( Figure 1C ), in aged rats. Also, aged rats demonstrated decreased von Frey sensitivity ( 14 , 15 ) to tactile (mechanical) stimuli, both abdominal (visceral; Figure 1D ) and cutaneous (hind paw; Figure 1E ). The von Frey test is a noninvasive behavioral method that uses a series of calibrated von Frey filaments to assess the sensitivity to mechanical stimuli (i.e., response to pressure stimuli) at various anatomical locations.…”
Section: Resultsmentioning
confidence: 99%
“…Montalbetti et al. showed that, in rats, increased urothelial permeability caused by disrupted urothelial tight junctions resulted in bladder afferent nerve hyperexcitability and upstream central nerve sensitization with few inflammatory changes, and without altering epithelial quantity or umbrella cell polarity/differentiation 130,131 . In contrast, emerging evidence has suggested a potential connection between bladder/pelvic hypersensitivity and psychological/physiological stress, involving functional alteration of the CNS, in humans.…”
Section: Animal Modelsmentioning
confidence: 99%